Security architecture for network virtualization in cloud computing. - Barros, Bruno Medeiros de (2016)
Network virtualization has been a quite active research area in the last years, aiming to tackle the increasing demand for high performance and secure communication in cloud infrastructures. In special, such research eforts have led to security solutions focused on improving isolation among multiple tenant of public clouds, an issue recognized as critical both by the academic community and by the technology Industry. More recently, the advent of Software-Defined Networks (SDN) and of Network Function Virtualization (NFV) introduced new concepts and techniques for addressing issues related to the isolation of network resources in multi-tenant clouds while improving network manageability and flexibility. Similarly, hardware technologies such as Single Root I/O Virtualization (SR-IOV) enable network isolation in the hardware level while improving performance in physical and virtual networks. Aiming to provide a cloud network environment that effciently tackles multi-tenant isolation, we present three complementary strategies for addressing the isolation of resources in cloud networks. These strategies are then applied in the evaluation of existing network virtualization architectures, exposing the security gaps associated to current technologies, and paving the path for novel solutions. We then propose a security architecture that builds upon the strategies presented, as well as upon SDN, NFV and SR-IOV technologies, to implement secure cloud network domains. The theoretical and experimental analyses of the resulting architecture show a considerable reduction of the attack surface in tenant networks, with a small impact over tenants\' intra-domain and inter-domain communication performance.